Familial hypophosphatemic rickets - Sattur A; Naikmasur V; Shrivastava R; Babshet M (Wolters Kluwer Medknow Publications, 2010)
Rickets is the failure of mineralization of osteoid and newly formed bones in a child skeleton. It is commonly associated with vitamin D deficiency; however, it can be because of a decrease in the serum phosphate levels leading to inadequate mineralization of cartilage and bone, consequent skeletal deformities, and growth retardation. The hypophosphatemic conditions that interfere in bone mineralization comprise many hereditary or acquired diseases. One of the hereditary types of hypophosphatemic rickets is the familial hypophosphatemic rickets. This rare variety was diagnosed in a 9-year-old patient who had come with a chief complaint of a missing tooth. In the present case, radiographic aspects of oral and systemic manifestations of familial hypophosphatemic rickets are highlighted.